(untitled) (Journal of history, 2023)
Abstract. The article analyses information from Arab sources of IX-XIII centuries about historical geography of the middle and lower reaches of the Syrdarya river. On the basis of works by such authors as al-Kharizmi (IX century), Ibn Khordadbek (IX century), Ibn al-Fakih (IX-X centuries), Abu Zayd al-Balkhi (X century), Ibn Haukal (X century), al-Muhallabi (X century), Hudud al-Alam (X century), al-Maqdisi (X century), al-Beruni (XI century), al-Idrisi (XII century), al-Samani (XII century), Yaqut al-Hamawi (XII century) information about the names and renaming of cities and settlements of the mentioned region and distances between them as well as their caravan routes, history and cultural life underwent comparative analysis with the results of recent archaeological studies. The works by Arab authors on the main cities of the Otyrar-Farab region Farab and Keder, as well as the cities of Usbaniket, Sutkent, Sauran, Syganak, Zhent, Zhankent were systematised and comprehensively analysed from a scientific point of view, and information on changes in their names, peculiarities of their location, population, etc. is given. The Arabic sources on the cities’ topography, economic role, peculiarities of their cultural and social life were subjected to comparative analysis and some of the information was presented for the first time. The paper also draws some conclusions regarding the concept of nomadism and the relationship between nomadic and sedentary lifestyles.